Double burden of malnutrition among non-pregnant women of reproductive age: Results from the National Health Survey of Panama (ENSPA) 2019 - Roger Montenegro Mendoza; Flavia Fontes; José Renán De León; Beatriz Gómez; Abdiel Bonilla; Fanny Franco; Bernardo González; Reina Roa; Hedley Quintana; Ilais Moreno Velásquez (PLOS One, 2026)
Background The co-occurrence of different forms of malnutrition has implications for human capital development, as the physiological effects of both anaemia and obesity have been associated with national economic and productivity indicators. This study aims to estimate the prevalence of the double burden of malnutrition including its component conditions, and to identify sociodemographic factors and inflammatory factors associated with the co-occurrence of overweight/obesity and anaemia among non-pregnant women of reproductive age in Panama. Methods Using data derived from the 2019 National Health Survey of Panama, we estimated the prevalence of overweight/obesity without anaemia, anaemia without overweight/obesity and the double burden of malnutrition, defined as the co-occurrence of overweight/obesity and anaemia, among non-pregnant women aged 15–49 years. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using multinomial logistic regression to assess the association between sociodemographic factors and the double burden of malnutrition. Results The weighted prevalence of double burden of malnutrition was 18.6% (95% CI: 15.9%−21.7%). In multivariate adjusted models, compared with women with neither OW/OB nor anaemia, lower vs. higher education (OR= 2.84; 95% CI: 1.24–6.53), ever-having given birth vs. never (OR= 3.01; 95% CI: 1.11–8.15), higher vs. lower inflammation (OR= 9.39; 95% CI: 4.85–18.19) and age 40–49 vs. younger age (OR= 5.99; 95% CI: 1.80–19.95) were associated with double burden of malnutrition. Low education and inflammation were associated with anaemia without overweight/obesity, while older age, indigenous areas, low education, and inflammation were associated with overweight/obesity. Conclusion Double burden of malnutrition affected almost one in five women of reproductive age in Panama. While living in indigenous area was associated with overweight/obesity without anaemia, low education and inflammation emerged as potential shared factors for the individual and combined forms of the double burden of malnutrition.